Rationale and Design of a Clinical Trial to Evaluate the Safety and Efficacy of Intracoronary Infusion of Allogeneic Human Cardiac Stem Cells in Patients With Acute Myocardial Infarction and Left Ventricular Dysfunction: The Randomized Multicenter Double-Blind Controlled CAREMI Trial (Cardiac Stem Cells in Patients With Acute Myocardial Infarction). Issue 1 (23rd June 2017) - Sanz-Ruiz, Ricardo; Casado Plasencia, Ana; Borlado, Luis R.; Fernández-Santos, María Eugenia; Al-Daccak, Reem; Claus, Piet; Palacios, Itziar; Sádaba, Rafael; Charron, Dominique; Bogaert, Jan; Mulet, Miguel; Yotti, Raquel; et al.
Abstract : Rationale: : Stem cell therapy has increased the therapeutic armamentarium in the fight against ischemic heart disease and heart failure. The administration of exogenous stem cells has been investigated in patients suffering an acute myocardial infarction, with the final aim of salvaging jeopardized myocardium and preventing left ventricular adverse remodeling and functional deterioration. However, phase I and II clinical trials with autologous and first-generation stem cells have yielded inconsistent benefits and mixed results. Objective: : In the search for new and more efficient cellular regenerative products, interesting cardioprotective, immunoregulatory, and cardioregenerative properties have been demonstrated for human cardiac stem cells. On the other hand, allogeneic cells show several advantages over autologous sources: they can be produced in large quantities, easily administered off-the-shelf early after an acute myocardial infarction, comply with stringent criteria for product homogeneity, potency, and quality control, and may exhibit a distinctive immunologic behavior. Methods and Results: : With a promising preclinical background, CAREMI (Cardiac Stem Cells in Patients With Acute Myocardial Infarction) has been designed as a double-blind, 2:1 randomized, controlled, and multicenter clinical trial that will evaluate the safety, feasibility, and efficacy of intracoronary delivery of allogeneic human cardiac stem cell in 55 patients with large acute myocardial infarction, left ventricular dysfunction, and at high risk of developing heart failure. Conclusions: : This phase I/II clinical trial represents a novel experience in humans with allogeneic cardiac stem cell in a rigorously imaging-based selected group of acute myocardial infarction patients, with detailed safety immunologic assessments and magnetic resonance imaging–based efficacy end points. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT02439398.